2011
DOI: 10.1074/jbc.m110.193359
|View full text |Cite
|
Sign up to set email alerts
|

An Infant-associated Bacterial Commensal Utilizes Breast Milk Sialyloligosaccharides

Abstract: Lactating mothers secrete milk sialyloligosaccharides (MSOs) that function as anti-adhesives once provided to the neonate. Particular infant-associated commensals, such as Bifidobacterium longum subsp. infantis, consume neutral milk oligosaccharides, although their ability to utilize acidic oligosaccharides has not been assessed. Temporal glycoprofiling of acidic HMO consumed during fermentation demonstrated a single composition, with several isomers, corresponding to sialylated lacto-Ntetraose. To utilize MSO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
129
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 177 publications
(133 citation statements)
references
References 52 publications
4
129
0
Order By: Relevance
“…Sialidases, which release sialic acid from glycans, have previously been described for infant-derived bifidobacteria, including two intracellular sialidases from B. longum subsp. infantis ATCC 15697 (34) and an extracellular sialidase from B. bifidum JCM1254 (78). Two predicted extracellular exo-␣-sialidases were also identified in the genome of B. bifidum PRL2010 (64).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Sialidases, which release sialic acid from glycans, have previously been described for infant-derived bifidobacteria, including two intracellular sialidases from B. longum subsp. infantis ATCC 15697 (34) and an extracellular sialidase from B. bifidum JCM1254 (78). Two predicted extracellular exo-␣-sialidases were also identified in the genome of B. bifidum PRL2010 (64).…”
Section: Discussionmentioning
confidence: 93%
“…1, were identified in the genome of Bifidobacterium longum subsp. infantis ATCC 15697, and in accordance, this strain was shown to be capable of utilizing sialic acid (33) or the HMO sialylated lacto-N-tetraose as a sole carbon source (34). A recent study of the consumption of HMOs by strains of B. breve revealed that all of those tested can utilize sialylated lacto-N-tetraose (35).…”
mentioning
confidence: 90%
“…Oligosaccharides were purified from a cranberry derivative through reverse-phase C 18 and size exclusion chromatography (see Fig. S1 in the supplemental material).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the chromosome of the phylogenetic near neighbor and infant-colonizing bacterium B. longum subsp. infantis contains genes that enable human milk oligosaccharide utilization within the nursing infant gut (15)(16)(17)(18). In general, B. longum subsp.…”
Section: Importancementioning
confidence: 99%
“…In addition, several different strategies are employed by groups of Bifidobacterium to utilize HMOs. B. infantis ATCC 15697 is believed to import HMOs intact and subsequently to employ intracellular glycoside hydrolases, such as ␤-galactosidases, N-acetyl-␤-D-hexosaminidases, ␣-fucosidases, and ␣-sialidases, to deconstruct HMOs (31)(32)(33)(34)(35). In contrast, other species of Bifidobacterium (e.g., B. bifidum) employ extracellular glycosidases to sequentially degrade these structures and to transport mono-, di-, or oligosaccharides rather than the complex, compositionally diverse, and often branched structures which comprise HMOs (31).…”
mentioning
confidence: 99%